2016
DOI: 10.1007/s00248-016-0825-6
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay Between Predation, Competition, and Nutrient Levels Influences the Survival of Escherichia coli in Aquatic Environments

Abstract: Nutrient levels, competition from autochthonous microorganisms, and protozoan predation may all influence survival of fecal microorganisms as they transition from the gastrointestinal tract to aquatic habitats. Although Escherichia coli is an important indicator of waterborne pathogens, the effects of environmental stressors on its survival in aquatic environments remain poorly understood. We manipulated organic nutrient, predation, and competition levels in outdoor microcosms containing natural river water, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…At lower nutrient concentrations, studies have shown that the presence of biota can confound the effect of nutrient addition in the water column (89, 92), diminishing the effect of nutrients on FIB persistence. This finding is consistent with those of another laboratory-based study in which the effect of organic carbon addition on FIB persistence was concentration dependent (90).…”
Section: Nutrientssupporting
confidence: 93%
See 2 more Smart Citations
“…At lower nutrient concentrations, studies have shown that the presence of biota can confound the effect of nutrient addition in the water column (89, 92), diminishing the effect of nutrients on FIB persistence. This finding is consistent with those of another laboratory-based study in which the effect of organic carbon addition on FIB persistence was concentration dependent (90).…”
Section: Nutrientssupporting
confidence: 93%
“…In particular, elevated indicator concentrations were observed when organic carbon levels were at or above 7 mg/liter (83). Other studies conducted using incremental levels of organic carbon also reported enhanced survival of E. coli in the water column (90,91). In both studies, the positive effect of nutrient addition on E. coli varied depending on nutrient levels and/or the presence of biota (predators and competitors) (90,91).…”
Section: Nutrientsmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, much of the biodiversity in the E. coli species may be generated and maintained via transient-to-semipermanent residence in extrahost habitats (7). This process can confound the use of E. coli as an indicator organism for fecal contamination in water quality testing (8,9). Therefore, understanding the ecology of E. coli in extrahost habitats can inform not only our environmental and public health policy but also our concept of microbial species.…”
mentioning
confidence: 99%
“…Decay of bacteria and fecal markers in sediments is particularly understudied even though sediments, soils, and beach sands have been implicated as potential reservoirs in a variety of climates and environments (Alm et al, 2014;Craig et al, 2004;Garzio-Hadzick et al, 2010;Haller et al, 2009;Lee et al, 2006). Sediments can promote persistence of fecal organisms both by providing protection from ultraviolet radiation, temperature fluctuations, and predation by microorganisms in the overlying water column (Davies et al, 1995;Korajkic et al, 2013;Wanjugi and Harwood, 2013;Wheeler Alm et al, 2003) and by supplying critical nutrients (Craig et al, 2004;Labelle et al, 1980;Mika et al, 2009;Wanjugi et al 2016). Under favorable sediment conditions, fecal indicator bacteria (FIB) exhibit extended survival and even regrowth, which can lead to false positive indications of recent fecal pollution in water quality monitoring when organisms colonize sediment and levels no longer correspond with the presence of fecal pollution and pathogens (Byappanhalli and Fujioka, 1998;Byappanahalli et al, 2012;Davies and Bavor, 2000;Garzio-Hadzick et al, 2010;Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%